2004
DOI: 10.1093/fampra/cmh705
|View full text |Cite
|
Sign up to set email alerts
|

Iron deficiency anemia in patients without gastrointestinal symptoms--a prospective study

Abstract: Our prospective study demonstrates a high rate of malignancy, predominantly right-sided colon carcinoma, in men older than 50 years and post-menopausal women with asymptomatic IDA. This finding obligates a complete and rigorous GI tract examination in this group of patients, especially of the right colon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
43
1
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 15 publications
9
43
1
3
Order By: Relevance
“…In contrast, elderly patients in our study revealed a prevalence of malignancies' association with IDA. Indeed, a high rate of colon malignancies, predominantly right-sided colon carcinoma in post-menopausal women and older men with asymptomatic IDA has been reported [21]. Our results also show the benign and malignant colon Cancer can be one of the important etiology of IDA and this is consistent with other studies [22].…”
Section: Discussionsupporting
confidence: 93%
“…In contrast, elderly patients in our study revealed a prevalence of malignancies' association with IDA. Indeed, a high rate of colon malignancies, predominantly right-sided colon carcinoma in post-menopausal women and older men with asymptomatic IDA has been reported [21]. Our results also show the benign and malignant colon Cancer can be one of the important etiology of IDA and this is consistent with other studies [22].…”
Section: Discussionsupporting
confidence: 93%
“…The levels of transferrin have been shown to increase in iron deficiency anemia [5,6]. Additionally, incidents of bleeding in cancer patients can result in iron deficiency anemia, which subsequently increases the levels of lactoferrin [79]. Furthermore, patients with iron deficiency anemia are about four times more susceptible to contracting pneumonia than non-anemic individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Although iron-deficiency anemia is a very common clinical problem, most studies have examined small, heterogenous cohorts of patients with varying demographic and anemia parameters (10). The present study focused on men !18 years old to investigate the various causes of irondeficiency anemia in a prospective fashion.…”
Section: Discussionmentioning
confidence: 99%